2013
DOI: 10.1007/s10640-013-9750-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Residential Water Demand with Imperfect Price Perception

Abstract: International audienceUsing data from a household survey carried out in the French overseas territory of Réunion, we investigate the price of drinking-water perceived by households faced with an increasing, multi-step pricing scheme. To this purpose we use an improved version of the method introduced by Shin (1985) to estimate the demand for residential water when consumers are imperfectly informed about their pricing schedule. The empirical results suggest that Réunion households underestimate the price of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 23 publications
1
45
0
2
Order By: Relevance
“…Shin (1985) introduces a price-perception concept that identifies which of the two prices (the marginal or the average price) is better understood by consumers. Few researchers have followed in his footsteps; the recent work by (Binet et al, 2014) proposes significant modifications to the functional form of Shin's perceived price. The reference category for this group of dummy variables is the average pricing scheme.…”
Section: Variables and Estimationmentioning
confidence: 99%
“…Shin (1985) introduces a price-perception concept that identifies which of the two prices (the marginal or the average price) is better understood by consumers. Few researchers have followed in his footsteps; the recent work by (Binet et al, 2014) proposes significant modifications to the functional form of Shin's perceived price. The reference category for this group of dummy variables is the average pricing scheme.…”
Section: Variables and Estimationmentioning
confidence: 99%
“…Schleich et al [8] found evidence that households respond psychologically to the fact that it rained rather than to the total amount of rainfall. In this sense, Binet et al [19] used the variable non-rainy days to explain the residential water demand for watering the garden. Therefore, we prefer to rely on the analysis with rainy days.…”
Section: The Effect Of the Reform On Water Consumption In The Three Hmentioning
confidence: 99%
“…Most empirical studies have also found that residential demand for water is influenced by heterogeneity associated with differences in the size of the household [12]. For France and Spain, it is reported that household size affects the demand for water, in general positively (i.e., [18,21,22,24,25,27]), although a few studies have found the inverse result (i.e., [13,19,26]). Climate is one of the most studied drivers of domestic water demand.…”
Section: Residential Water Demand In France and Spain: A Brief Reviewmentioning
confidence: 99%
“…For France and Spain, it is found that water use increases with temperature (i.e., [12,17,19,22,23]) or with the number of dry days (i.e., [17]). On the contrary, water consumption decreases with rainfall levels (i.e., [18,19,24]). …”
Section: Residential Water Demand In France and Spain: A Brief Reviewmentioning
confidence: 99%